2022
DOI: 10.1002/tpg2.20201
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation and underlying genetic loci of γ‐oryzanol in Asian cultivated rice seeds

Abstract: γ-oryzanol is the most studied component in rice (Oryza sativa L.) bran oil. It is not only associated with physiological processes of rice growth and development but also grain quality that is related to human health. Previous studies focused mainly on γ-oryzanol composition and content in various rice cultivars, while its biosynthetic and regulatory pathways remain unknown. Here we present the quantitative identification of γ-oryzanol in rice seeds across 179 Asian cultivated accessions using ultra-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…To clarify the QTLs for the concentrations of 1, 2 , and total γ‐oryzanol, we investigated the mapping populations from a cross between cultivars Momiroman and Takanari. A recent genome‐wide association study using Asian cultivars reported 13 candidate genes for the concentrations of 1 – 4 and total γ‐oryzanol on chromosomes 1, 3, 6, 7, 9, and 12 (Sun et al, 2022). However, in the present study, we detected the QTLs for the concentrations of 1, 2 , and total γ‐oryzanol on chromosomes 4, 5, 9, 10, and 11 (Figures 5–8).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the QTLs for the concentrations of 1, 2 , and total γ‐oryzanol, we investigated the mapping populations from a cross between cultivars Momiroman and Takanari. A recent genome‐wide association study using Asian cultivars reported 13 candidate genes for the concentrations of 1 – 4 and total γ‐oryzanol on chromosomes 1, 3, 6, 7, 9, and 12 (Sun et al, 2022). However, in the present study, we detected the QTLs for the concentrations of 1, 2 , and total γ‐oryzanol on chromosomes 4, 5, 9, 10, and 11 (Figures 5–8).…”
Section: Discussionmentioning
confidence: 99%
“…The natural genetic variations for γ-oryzanol in grains of different rice germplasms were explored previously by several studies ( 11 , 12 , 28 , 29 ). Nevertheless, there are scanty evidences on the spatial and temporal pattern of γ-oryzanol accumulation in rice.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC-MS experiments were performed as previously described (Pu et al, 2020; Sun et al, 2022). Briefly, samples from different brain regions after mouse sacrifice were homogenized in ice-cold 0.2M perchloric acid/methanol, sonicated (Bioruptor) and centrifuged at 10000 g for 20 mins.…”
Section: Methodsmentioning
confidence: 99%